2018
DOI: 10.1155/2018/3720813
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Male Sexual Function: A Transversal and Longitudinal Study

Abstract: Background The effects of vitamin D on sexual function are very unclear. Therefore, we aimed at evaluating the possible association between vitamin D and sexual function and at assessing the influence of vitamin D administration on sexual function. Methods We retrospectively studied 114 men by evaluating clinical, biochemical, and sexual parameters. A subsample (n = 41) was also studied longitudinally before and after vitamin D replacement therapy. Results In the whole sample, after performing logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
1
23
0
2
Order By: Relevance
“…Notably, we observed a significant association between higher vitamin D levels and higher testosterone concentrations only in men older than 56 years of age. Previous studies have yielded conflicting results regarding associations between testosterone and vitamin D levels [15][16][17]. Our results therefore suggest the possibility that the age of subjects may play an important role in accounting for some of the variations in vitamin D levels that have been previously observed.…”
Section: Discussionmentioning
confidence: 49%
“…Notably, we observed a significant association between higher vitamin D levels and higher testosterone concentrations only in men older than 56 years of age. Previous studies have yielded conflicting results regarding associations between testosterone and vitamin D levels [15][16][17]. Our results therefore suggest the possibility that the age of subjects may play an important role in accounting for some of the variations in vitamin D levels that have been previously observed.…”
Section: Discussionmentioning
confidence: 49%
“…One study included 102 males having vitamin D levels under 30 ng/ml, with a 12-month follow-up that received vitamin D replacement therapy, and found both self-reported IIEF-5 score and serum testosterone levels exhibited a stepladder increases in the follow-up duration (Canguven, Talib, Ansari, Yassin, & Al Naimi, 2017). Along with this same line, erection function showed a significant improvement after vitamin D replacement therapy in another longitudinal study (Tirabassi et al, 2018). However, in another study cohort, assessing the effect of vitamin D supplementation in dialysis patients, there were no significant changes in sexual parameters (Blumberg et al, 1980).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, 13 were found suitable for inclusion in this study. Three of these latter studies were excluded for the study design: they were intervention studies [13][14][15]. The articles by Bellastella and colleagues [17] and Zhang and colleagues [18] were excluded because we could not extract useful data for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The few studies of this type have given conflicting results. In fact, Tirabassi and colleagues have shown that vitamin D supplementation, given until normal circulating levels were restored, is associated with an improvement in ED that is independent of circulating testosterone levels [13]. Similarly, Canguven and colleagues estimated that supplementation with 600,000 units of ergocalciferol per month for 12 months is associated with a progressive improvement in ED and an increase of serum testosterone levels [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation